MATHEMATICAL THINKING DAN KAITANNYA DENGAN WAYS OF UNDERSTANDING, WAYS OF THINKING: SEBUAH KAJIAN PUSTAKA - Wilda Syam Tonra; Talisadika S. Maifa; Willy Abdul Ghany; Siti Fatimah (SIGMA, 2023)
Abstrak:Awal munculnya istilah “Mathematical Thinking” merujuk kepada istilah dari buku yang sangat terkenal berjudul Thinking Mathematically dengan jumlah sitasi saat ini mencapai 1781. Buku ini ditulis oleh John Mason dengan Leone Burton dan Kaye Stacey tahun 1982. Buku ini menjadi rujukan dari beberapa peneliti lainnya. Di buku ini, Mathematical Thinking proses dibagi menjadi 2 pasang proses yaitu Specialising and Generalising kemudian Conjecturing and Convincing. Namun, istilah “Mathematical Thinking”memiliki beberapa pergeseran makna sesuai dengan perkembangan dari tahun ke tahun. Selain itu, paper ini juga membahas kaitan antara “Mathematical Thinking” atau berpikir matematis dengan ways of understanding dan ways of thinking. Kata Kunci: Mathematical Thinking; ways of understanding; ways of thinking Abstract:Early term of "Mathematical Thinking" refers to the term from a very famous book entitled Thinking Mathematically with the current number of citations reaching 1781. This book was written by John Mason with Leone Burton and Kaye Stacey in 1982. This book became a reference for several other researchers. In this book, the Mathematical Thinking process is divided into 2 pairs of processes, namely Specializing and Generalising then Conjecturing and Convincing. However, the meaning of mathematical thinking has changed according to developments from year to year. In addition, this paper also discusses the relationship between "Mathematical Thinking" with ways of understanding and ways of thinking.conclusions.